Determinants of adherence and consequences of the transition from adolescence to adulthood among young people with severe haemophilia (TRANSHEMO): study protocol for a multicentric French national observational cross-sectional study. Issue 7 (25th July 2018) - Resseguier, Noémie; Rosso-Delsemme, Natacha; Beltran Anzola, Any; Baumstarck, Karine; Milien, Vanessa; Ardillon, Laurent; Bayart, Sophie; Berger, Claire; Bertrand, Marie-Anne; Biron-Andreani, Christine; Borel-Derlon, Annie; Castet, Sabine; et al.
Abstract : Introduction: Severe haemophilia is a rare disease characterised by spontaneous bleeding from early childhood, which may lead to various complications, especially in joints. It is nowadays possible to avoid these complications thanks to substitutive therapies for which the issue of adherence is major. The transition from adolescence to adulthood in young people with severe haemophilia is a critical period as it is associated with a high risk of lack of adherence to healthcare, which might have serious consequences on daily activities and on quality of life. Methods and analysis: We present the protocol for a cross-sectional, observational, multicentric study to assess the differences between adolescents and young adults with severe haemophilia in France through the transition process, especially on adherence to healthcare. This study is based on a mixed methods design, with two complementary and consecutive phases, comparing data from a group of adolescents (aged 14–17 years) with those from a group of young adults (aged 20–29 years). The quantitative phase focuses on the determinants (medical, organisational, sociodemographic and social and psychosocial and behavioural factors) of adherence to healthcare (considered as a marker of the success of transition). The qualitative phase explores participants' views in more depth to explain and refine the results from the quantitative phase. Eligible patients are contacted by the various Haemophilia Treatment Centres participating in the French national registry FranceCoag. Ethics and dissemination: The study was approved by the French Ethics Committee and by the French National Agency for Medicines and Health Products Safety (number: 2016-A01034-47). Study findings will be disseminated to the scientific and medical community in peer-reviewed journals and presented at scientific meetings. Results will be popularised to be communicated via the French association for people with haemophilia to participants and to the general public. Trial registration number: NCT02866526 ; Pre-results.